IL-6 and PD-1 antibody blockade combination therapy regulate inflammation and T lymphocyte apoptosis in murine model of sepsis - Song I Lee; Na Young Kim; Chaeuk Chung; Dongil Park; Da Hyun Kang; Duk Ki Kim; Min-Kyung Yeo; Pureum Sun; Jeong Eun Lee (BMC Immunology)
Abstract Background Interleukin-6 (IL-6) plays a central role in sepsis-induced cytokine storm involving immune hyperactivation and early neutrophil activation. Programmed death protein-1 (PD-1) is associated with sepsis-induced immunosuppression and lymphocyte apoptosis. However, the effects of simultaneous blockade of IL-6 and PD-1 in a murine sepsis model are not well understood. Results In this study, sepsis was induced in male C57BL/6 mice through cecal ligation and puncture (CLP). IL-6 blockade, PD-1 blockade, or combination of both was administered 24 h after CLP. Peripheral blood count, cytokine level, lymphocyte apoptosis in the spleen, neutrophil infiltration in the lungs and liver, and survival rate were measured. The mortality rate of the IL-6/PD-1 group was lower, though not statistically significant (p = 0.164), than that of CLP mice (75.0% vs. 91.7%). The IL-6/PD-1 group had lower neutrophil percentage and platelet count compared with the CLP group; no significant difference was observed in other cytokine levels. The IL-6/PD-1 group also showed reduced T lymphocyte apoptosis in the spleen and decreased neutrophil infiltration in the liver and lungs. Conclusions IL-6/PD-1 dual blockade reduces neutrophil infiltration, lymphocyte apoptosis, and bacterial burden while preserving tissue integrity in sepsis. Although the improvement in survival was not statistically significant, these findings highlight its potential as a therapeutic approach in sepsis.